Kinetics of Lactic Acid Fermentation during Dahi Preparation (Tribhuvan University Journal of Food Science and Technology, 2022)
Dahi with 4.15% fat and 11% solids-not-fat (SNF) was prepared from cow milk, pasteurized at 85℃ for 15 min and cooled to 25℃. Fermentation kinetics was studied to study the effects of sugar concentration (2 to 10%) and starter-level (1 to 3%) on cell growth, lactic acid production and its rate, pH, and lactic acid bacteria (LAB) count which was monitored every 3 h until the total of 15 h fermentation time. The biomass growth rate was very high for 10% sugar at 2% inoculum levels i.e., lnX/Xt = 30.74. Similarly, the lactic acid production rate was maximum (0.17%) for 2% sugar at 1% inoculum level. The overall maximum growth rate was observed at 6% sugar concentration for all inoculum concentrations. The highest growth rate of 0.8 per hour was seen for 1% inoculum at 6% sugar concentration and the pH for the entire process decreased from 6.5 to 4.4 when fermented at room temperature (28℃). The decrease was steep and a gradual fall in pH was obtained at 8 h of fermentation in 2% and 8% sugar levels at all inoculum levels. From the study, inoculation and sugar levels showed a significant effect on the specific growth rate, pH, and the total lactic acid bacterial counts thereby heading one step possibility of commercialization of indigenous product dahi through optimization of the process variables.